2001
DOI: 10.1007/s002490000114
|View full text |Cite
|
Sign up to set email alerts
|

Calcium-dependent association of annexins with lipid bilayers modifies gramicidin A channel parameters

Abstract: In order to examine whether calcium-dependent binding of annexin to acidic phospholipids could change the lipid bilayer environment sufficiently to perturb channel-mediated transmembrane ion-transport, gramicidin A channel activity in planar lipid bilayers was investigated in the presence of calcium and annexins II, III or V. The experiments were performed with membranes consisting of phosphatidylcholine, phosphatidylethanolamine and phosphatidylserine in 300 mM KCl solution buffered to pH 7.4 and with either … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2003
2003
2012
2012

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…Each of these annexins has a divergent N-terminal ''head'' which is variable and modulates protein binding (Hofmann et al, 2000;Sopkova et al, 2002), and a conserved C-terminal protein core which forms the calcium and membrane binding sites. In vitro, annexins have been implicated in membrane stabilization, ion channel activity (Eskesen et al, 2001), and mediation of membrane-membrane and membrane-cytoskeleton interaction (Diakonova et al, 1997). They also have a role in exocytosis and membrane trafficking and are associated with anti-inflammation and calcium-signaling mediators (Diakonova et al, 1997).…”
Section: Discussionmentioning
confidence: 98%
“…Each of these annexins has a divergent N-terminal ''head'' which is variable and modulates protein binding (Hofmann et al, 2000;Sopkova et al, 2002), and a conserved C-terminal protein core which forms the calcium and membrane binding sites. In vitro, annexins have been implicated in membrane stabilization, ion channel activity (Eskesen et al, 2001), and mediation of membrane-membrane and membrane-cytoskeleton interaction (Diakonova et al, 1997). They also have a role in exocytosis and membrane trafficking and are associated with anti-inflammation and calcium-signaling mediators (Diakonova et al, 1997).…”
Section: Discussionmentioning
confidence: 98%
“…Other approaches have demonstrated that single channel recordings can report molecular binding events. For instance, binding of proteins to lipids in a membrane typically affects the structure of the lipid bilayer and leads to changes in the kinetics of pore formation by biological pores such as gramicidin [195,303]. Using this effect, Hirano et al detected antibody binding to antigen-decorated lipids (Figure 9b) [195].…”
Section: Applications Of Biological Pores For Sensingmentioning
confidence: 99%
“…Using this effect, Hirano et al detected antibody binding to antigen-decorated lipids (Figure 9b) [195]. Another study by Bennekou and co-workers monitored calcium-dependent binding of the peripheral membrane protein annexin [83,304] to lipid membranes; in this case, the resulting changes in the lifetime and single channel conductance of gramicidin pores provided the signal [303]. …”
Section: Applications Of Biological Pores For Sensingmentioning
confidence: 99%
“…The single RyR2 molecule electrophysiological results with and without 1 μM annexin A5 show that annexin A5 has minimal effect on either the open probability (Po) or conductance (Figure ). In contrast, Eskesen et al reported that annexin A5 decreases the conductance of gramicidin A, concluding diffusion resistance increases in the gramicidin A channel mouth . This is likely because gramicidin A has a small cylindrical radius in the transmembrane region, meaning annexin A5 binding to the lipid can easily access the ion pathway of this peptide channel.…”
Section: Discussionmentioning
confidence: 94%